1995
DOI: 10.2118/24936-pa
|View full text |Cite
|
Sign up to set email alerts
|

EOS Modeling and Experimental Observations of Three-Hydrocarbon-Phase Equilibria

Abstract: An equation-of-state (EOS) fluid characterization has been developed to model three-hydrocarbon-phase equilibria. The fluid characterization was developed as part of the enriched-gas EOR research program for the Kuparuk hydrocarbon miscible flood on the North Slope of Alaska. Laboratory experiments with the Kuparuk fluid system have quantitatively identified the third hydrocarbon phase as a second equilibrium liquid, high in asphaltene content and heavier than the original oil. A three-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…have been conducted. The 2Z-04 oil has a low asphaltene content, while the 1E-08 oil, whose composition is reported by Godbole et al, (1992) has one of the richer asphaltene contents in the field. The slimtube results indicated that the two oils have essentially the same minimum miscibility enrichment (MME) level (see Fig.…”
Section: Phase Behaviourmentioning
confidence: 91%
See 2 more Smart Citations
“…have been conducted. The 2Z-04 oil has a low asphaltene content, while the 1E-08 oil, whose composition is reported by Godbole et al, (1992) has one of the richer asphaltene contents in the field. The slimtube results indicated that the two oils have essentially the same minimum miscibility enrichment (MME) level (see Fig.…”
Section: Phase Behaviourmentioning
confidence: 91%
“…The EOS developed by Godbole et al (1992) predicts the formation of a second, more viscous, liquid hydrocarbon phase. The three hydrocarbon phases exist over a relatively large portion of the phase envelope.…”
Section: Phase Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest from a modelling perspective is the nature of the instability responsible for the precipitation of asphaltene-rich phases for which both solid-liquid [48,49] and liquid-liquid [50] immiscibilities have been suggested, which has given rise to some disagreement in the approach to model these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Scatchard-Hildebrand [7], Flory-Huggins [7,36], and Scott-Magat [37] polymer solution theories) to model phase behavior of asphaltenecontaining fluids [1,2,5,7,8,14,[20][21][22][23]. In addition to these models, there are also other models, which are based on cubic equations of state [17,24]. New thermodynamic models have recently been developed, which can take into account the micellar / aggregation natures of asphaltenes [5,13,16,[26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%